Jati Diri, Citra, dan Jaminan Kualitas Lembaga Pendidikan Islam - Makmur Sukri; Riswan Batu (Transformasi Manageria Journal of Islamic Education Management, 2024)
The purpose of writing this article is to find out the importance of institutional identity, image and quality assurance of Islamic educational institutions. This research uses the library research method, namely researching library materials or literature related to the research problem by selecting, reading, reviewing and researching books or other relevant written sources. The results of the research explain that Islamic educational institutions show themselves not only as educational institutions, but also include Islamic identity and the identity of Muslims. Ways to grow the image of Islamic educational institutions are educational publications, forming public opinion, and marketing education. Guaranteeing the quality of educational institutions can be seen from the implementation of quality assurance for Islamic education which is directed at the National Education Standards.